Computations of the flow past a still sphere at moderate reynolds numbers using an immersed boundary method - Campregher, Rubens; Militzer, Julio; Mansur, Sérgio Said [UNESP]; Da Silveira Neto, Aristeu (Springer Nature, 2009)
This paper presents an immersed boundary formulation for three-dimensional incompressible flows that uses the momentum equation to calculate the Lagrangian force field indirectly imposing the no-slip condition on solid interfaces. In order to test the performance of this methodology the flow past a sphere for Reynolds numbers up to 1,000 have been calculated. Results are compared with numerical data from other authors and empirical correlations available in the literature. The agreement is found to be very good. Copyright © 2009 by ABCM.
Keywords: Flow past sphere; Immersed boundary method; Transitional flow; Virtual physical model